Balancing two wheeled using Arduino microcontroller / Saiful Amirul Asyraf Mohd Halid - Mohd Halid, Saiful Amirul Asyraf (2020)
Most of two-wheeled self-balancing robot are designed based on an inverted pendulum system, which is the dynamically system stable but not for steadily system. The robot involves various physic and control parameters such as Linear Quadratic Regulator (LQR). The project aims to design the modelling parameter in order to control the balancing of two-wheeled self-balancing robot. A sensor, which is called as IMU was used to estimate and will be obtain the tilt angle of the robot. Then PID concept was applied to correct the error between the desired set point and the actual tilt angle position can adjust the motor speed accordingly to balance and stable the robot. The result that obtained from the PID controller show that this robot was able to balance the system acceptably but with some limitations. The PID controller was implemented using Arduino microcontroller. The limitation of this project is the size of project is too high and highly cost. The simulation result of the model is compared with the developed prototype and performance of the controller is analyzed and discussed. In addition, the PID tuning using heuristic method is also performed and an improvement can clearly be seen in terms of the robot balancing.